2001
DOI: 10.2105/ajph.91.4.639
|View full text |Cite
|
Sign up to set email alerts
|

Elective amniocentesis in low-risk pregnancies: decision making in the era of information and uncertainty

Abstract: A B S T R A C TObjectives. Rational choice theory was applied to explain women's use of amniocentesis. Variables included knowledge about prenatal diagnostics, attitudes, and emotional preferences.Methods. Using structured instruments at 9 to 14 and at 29 to 34 weeks' gestation, we interviewed 232 Israeli women who had low-risk pregnancies.Results. Women who had elective amniocentesis (n=39) were more knowledgeable about prenatal diagnostics, risks of invasive procedures, and probability of fetal abnormality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This finding is in agreement with an earlier report in which preliminary knowledge about prenatal testing was associated with increased test rates [12]. The authors of that study found that women who underwent elective amniocentesis were more knowledgeable about prenatal diagnostics and the risks and probability of abnormality than those who were referred for but did not undergo medically indicated amniocentesis.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with an earlier report in which preliminary knowledge about prenatal testing was associated with increased test rates [12]. The authors of that study found that women who underwent elective amniocentesis were more knowledgeable about prenatal diagnostics and the risks and probability of abnormality than those who were referred for but did not undergo medically indicated amniocentesis.…”
Section: Discussionsupporting
confidence: 92%
“…Previous work has suggested several factors that predict test uptake: positive attitudes toward prenatal diagnostic tests, perception of prenatal diagnostic tests as reliable, and requests for more scientific information [ 25 ]. A study conducted in Israel found that use of amniocentesis by low risk women was associated with older age and receipt of more information about the test [ 26 ]. Others have shown that negative perceptions of having a child with DS had a more significant influence on decisions than the numeric probability of having such a child, as indicated by screening results [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient-level factors such as preferences [52, 53], health literacy [54], medical/psychological conditions [55, 56], and wealth [57, 58] are likely to have broad effects on overuse, as are differences in providers’ skills [59, 60], financial interests [61], and other cultural factors [59, 6265]. Measuring systematic overuse would also provide insight on the role of tort litigation and the practice of defensive medicine [66], and would elucidate industry’s function in resource utilization [67].…”
Section: How Can Measuring Systematic Overuse Have An Impact?mentioning
confidence: 99%